What is the present role for general practitioners in dementia care? Experiences of general practitioners, patients and family carers in Portugal - Balsinha, Conceição (2020)
Background: Governments are being challenged to integrate at least part of dementia care into primary care. However, little is known about the current role of general practitioners (GPs) regarding dementia care, especially in countries that do not have dementia strategies in place. The aim of this study was to explore the experiences of GPs, persons with dementia and their family carers in Portuguese primary care settings, to better understand GPs’ contribution to dementia care. Methods: A qualitative interview study of participants recruited from six practices in different social contexts within the Lisbon metropolitan area was carried out. Purposive sampling was used to recruit GPs, persons with dementia and carers. Interviews with GPs explored dementia care comprehensiveness, including satisfactory and challenging aspects. Interviews with patients and carers explored the experience of talking to GPs about cognitive impairments and related difficulties and the type of help received. Thematic analysis of interview transcripts was carried out using the framework approach. Results: Five major themes were identified: GPs have a limited contribution to dementia care, the case of advanced dementia, doctor–patient relationships, doctor–carer relationships and management of chronic conditions other than dementia. Conclusion: General practitioners seemed to contribute little to dementia care overall, particularly regarding symptom management. The exception was patients with advanced stages of dementia, given that specialists no longer followed them up. Remarkably, GPs seemed to be alone within primary care teams in providing dementia care. These findings strongly suggest that Portuguese primary care is not yet prepared to comply with policy expectations regarding the management of dementia.